2021
DOI: 10.3389/fsurg.2021.713171
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Recovery After Surgery for Patients Undergoing Cytoreductive Surgery and Hyperthermic Intraperitoneal Chemotherapy: A Systematic Review and Meta-Analysis

Abstract: Background: Cytoreductive surgery (CRS) and hyperthermic intraperitoneal chemotherapy (HIPEC) is a promising approach for the management of peritoneal carcinomatosis, but is associated with significant morbidity and prolonged hospital stay. Herein, we review the impact of Enhanced recovery after surgery (ERAS) protocol on length of stay (LOS) and early complications in patients undergoing CRS and HIPEC for peritoneal carcinomatosis.Methods: PubMed and Embase were searched for studies comparing ERAS protocol wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 41 publications
(60 reference statements)
2
4
0
Order By: Relevance
“…The major morbidity rate reported in our study (22.7%) is comparable to the most recent literature [ 37 , 38 ].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The major morbidity rate reported in our study (22.7%) is comparable to the most recent literature [ 37 , 38 ].…”
Section: Discussionsupporting
confidence: 89%
“…Finally, a recent review of the impact of ERP, including six retrospective studies, showed that implementing an ERP after CCRS with HIPEC is feasible and may decrease the HLS (MD: −2.82 95% CI: −3.79, −1.85 I2=29% p<0.00001) as well as the major morbidity rates of Clavien‒Dindo III/IV (RR: 0.60 95% CI: 0.41, 0.87 I2=0% p=0.007) compared to the control group [ 38 ]. However, the findings only suggest that ERP after CCRS with HIPEC is not associated with increased readmission, reoperation, or mortality rates.…”
Section: Discussionmentioning
confidence: 99%
“…Enhanced Recovery After Surgery (ERAS) protocols are effective at improving outcomes after surgery (1)(2)(3)(4) , but no standardized ERAS protocols exist in liver transplantation (LT) (5,6) . In addition, LT has some peculiarities with respect to other surgical procedures, given that per the intrinsic features of therapy, a large proportion of patients will be in poor condition (relative to elective surgery) at the moment of surgery.…”
Section: Introductionmentioning
confidence: 99%
“…There was also a significant reduction in time to first flatus of 0.8 days. Further meta-analysis revealed similar results for emergency laparotomy [40] and for pancreatoduodenectomy [41] with an associated reduction of delayed gastric emptying, as well as for cytoreductive surgery and hyperthermic intraperitoneal chemotherapy [42], liver resection [43], and even for liver transplantion [44] where a 55% reduction in intensive care unit was associated with the application of ERAS concept. A summary of all most recent meta-analysis for each surgical specialty is provided on Table 1.…”
Section: Clinical Outcomementioning
confidence: 78%